Speech-Driven Academic Records Delivery System - Parupati, Kavitha; Reddy Kaithi, Raghavendhar (Journal of Neonatal Surgery, 2025)
An Interactive Voice Response System (IVRS) is a computerized system employing pre-recorded or dynamically synthesized voice for interaction with users via speech recognition or DTMF (Dual-Tone Multi-Frequency) input offered through a phone keypad. In this project, we have a robust automation system for the issuing of academic records and certificates through IVRS technology. The users can place orders and pay for academic documents through simple voice commands or keypad inputs. The system conveys live academic information and intelligently forwards the caller to the appropriate department or service depending on their input. DTMF tones uttered over telephone keypads and speech recognition systems are utilized to accurately interpret user decisions and instructions. Furthermore, text-to-speech (TTS) technology is employed to render complex and dynamic text-based academic information into voice. This IVRS system reduces human effort to a significant extent while enhancing the user experience by making sure the callers reach exactly what they need. Once configured, the system operates without human intervention and can deliver 24/7 service to the users. Overall, this voice system is an affordable, effective, and scalable means for schools to provide a personalized and automated service experience.